Emerging Trends and Hot Spots of Electrical Impedance Tomography Applications in Clinical Lung Monitoring - Li, Zhe; Qin, Shaojie; Chen, Chen; Mei, Shuya; Yao, Yulong; Zhao, Zhanqi; Li, Wen; Deng, Yuxiao; Gao, Yuan (Frontiers in Medicine, 2022)
Objective: The aim of the study was to explore the emerging trends and hot topics concerning applications on electrical impedance tomography (EIT) in clinical lung monitoring Methods: Publications on EIT applications in clinical lung monitoring during 2001-2021 were extracted from Web of Science core collection. The search strategy was “electrical impedance tomography” and “lung”. CiteSpace, VOS viewer were used to study the citation characteristics, cooperation and keywords co-occurrence. Moreover, co-cited reference clustering, structural variation analysis and future research trends were demonstrated. Results: A total of 636 publications were included for final analysis. The global annual publications on clinical lung monitoring gradually increased during the last 2 decades. Germany contributed largest number of publications (32.2%) and has the most international collaboration. University Medical Center Schleswig-Holstein (84 Publications, cited frequency 2205),Physiological Measurement (105 publications, cited frequency 2056),Inéz Frerichs （116 articles, cited frequency 3609 ）were the institution, journal ,author with the largest number of articles citations and international collaboration network in the research field. “electrical impedance tomography” (occurrences, 304), “mechanical ventilation” (occurrences, 99), “acute respiratory distress syndrome” (occurrences, 67) are top3 most frequent keywords, “non-invasive monitoring” (Avg, pub, year: 2008.17) and “extracorporeal membrane oxygenation” (Avg, pub, year: 2019.60) were the earliest and latest keywords. Keyword “electrical impedance tomography” (strength 7.88) and co-cited reference “Frerichs I,2017, THORAX” (strength 47.45) had the highest burst value. “driving pressure”, “respiratory failure”, “titration” are 3 keywords still maintained high brush value until now. The largest and smallest cluster of the Co-cited reference are “obstructive lung diseases” ( #0,size:97）,” lung perfusion”（#20,size:5）. Co-cited reference “Frerichs I, 2017, THORAX” (modularity change rate:98.49), has the highest structural variability. Categories with most and least interdisciplinary crossing are “ENGINEERING” and “CRITICAL CARE MEDICINE”. Conclusions: EIT is a valuable technology for clinical lung monitoring, gradually convert from imaging techniques to the clinic. Research hotspots may continue in monitoring techniques, ventilation distribution of ARDS and respiratory therapy strategies. More diversified lung function monitoring such as lung perfusion and interdisciplinary crossing are potential emerging research trends.